2009
DOI: 10.1097/gme.0b013e3181857979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-dose isoflavones on metabolic and inflammatory markers in healthy postmenopausal women

Abstract: Context-After menopause, women experience changes in body composition, especially increase in fat mass. Additionally, advancing age, decreased physical activity and increased inflammation may predispose them to develop type-2 diabetes. Isoflavones have been shown to improve metabolic parameters in postmenopausal women. However, the effect of isoflavones on adipo-cytokines remains unclear.Objective-To evaluate the effect of high dose isoflavones on inflammatory and metabolic markers in postmenopausal women.Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 29 publications
3
100
2
1
Order By: Relevance
“…Studies have shown that soy protein isolate regulated adipose mRNA expression levels of adipocytokines in Wistar rats (Nagasawa et al, 2003). In addition, it has also been reported that soy isoflavones regulated serum leptin, TNFa and adiponectin in postmenopausal women (Charles et al, 2009;Llaneza et al, 2011). Furthermore, serum adiponectin in male monkeys was affected by soy isoflavones (Wagner et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that soy protein isolate regulated adipose mRNA expression levels of adipocytokines in Wistar rats (Nagasawa et al, 2003). In addition, it has also been reported that soy isoflavones regulated serum leptin, TNFa and adiponectin in postmenopausal women (Charles et al, 2009;Llaneza et al, 2011). Furthermore, serum adiponectin in male monkeys was affected by soy isoflavones (Wagner et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…By regulating the physiologic actions of various tissues or organs, adipokines and myokines play critical roles in regulating lipid and carbohydrate metabolism (Havel, 2004). Some of the adipokines in the blood of postmenopausal women and male monkeys have been reported to be regulated by soy isoflavones (Wagner et al, 2008;Charles et al, 2009;Llaneza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that chronic oxidative stress, generated through the oxidation of cytotoxic free fatty acids, could lead to upregulation of cytokines such as TNF-α and IL-6 [20]. A previous study reported that consumption of soy milk containing isoflavones lowered the level of circulating TNF-α in postmenopausal women, and the investigators suggested that the isoflavones were the active components in soy responsible for this effect [21]. In this study, genistein significantly decreased the serum TNF-α and IL-6 levels in NASH rats induced by HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavone has inhibited nuclear factor-kappa B (NFκB) pathway, mitogen-activating protein (MAP) kinase and several cellular signaling, so could decreased the expression of pro-inflammatory cytokines IL-1, IL-8, and tumor necrosis factor (TNF)-α. Results studies found that isoflavone inhibited inflammatory response [19][20][21][22][23]. Another study used rat brain tissue has found that soy isoflavone was able to reduce TLR-2 levels [23].…”
Section: Introductionmentioning
confidence: 99%